Management of Zakah Distribution: Empirical Evidence From Indonesia - Rahmatina A. Kasri (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2017)
Despite the importance of zakah distribution, few studies attempt to evaluate practices in managing the distribution. The paper, thus, aims to explore approaches and evaluate practices in managing the zakah distribution. It employs qualitative research approach with semi-structured interviews with key management personnel of seven largest zakah organizations in Indonesia. The main finding identifies two approaches in distributing zakah in Indonesia, namely consumptive disbursement and productive utilization approaches. Each approaches is different in terms of purpose/expected impact, types/nature of programs and methods of distributing the zakah proceeds. It is also found that different types of zakah organizations tend to focus on different zakah distribution approach. Moreover, some challenges are identified particularly in relation to selection/coverage of mustahik and threat or ‘competition’ in distributing zakah funds. Overall, the study highlights the increasing relevance of productive utilization approach as well as importance of enhancing outreach and availability of information related to zakah programs (including through online platforms) and continuously educate all zakah stakeholders. The findings are expected to provide insights in managing zakah distribution in Indonesia and ultimately in increasing effectiveness of zakah institution to achieve its objectives.Keywords: Indonesia, qualitative research, zakah distribution, zakah management, zakah organizations